Enlightened common sense I: clarifying and developing the concepts of depth, emergence, and transfactuality. Issue 1 (1st January 2019) - Holland, Dominic
ABSTRACT: This article is the first in a series of four articles that engage critically with the arguments of two recent and significant additions to the literature on critical realism, namely Bhaskar's 'Enlightened Common Sense: The Philosophy of Critical Realism', and Bhaskar et al.'s 'Interdisciplinarity and Wellbeing: A Critical Realist General Theory of Interdisciplinarity'. Using the method of immanent critique and focusing mainly, but not exclusively, on the arguments of Enlightened Common Sense, I identify, and propose solutions to, a range of problems pertaining to the concepts of depth, emergence and transfactuality. In identifying and resolving these problems, my aim is to clarify and develop the categories of original critical realism and thereby ensure that critical realism as a whole is as effective an underlabourer for science as it can be.